(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2026)
Gula apong is a type of traditional sugar made from Nypa fruticans, a type of palm that can be found abundantly at coastal areas of Sarawak. Gula apong is processed and produced under a small hut known as langko, which is built in the N. fruticans forest. The current condition of existing langko is in a state of disrepair and neglect, marked by the absence of proper access roads, no clean water supply, no electricity, poor building structures, inadequate hygiene, and an inconvenient layout. The paper aims to improve the design of the gula apong langko to help sustain the gula apong industry with two main objectives: (1) to identify sustainable features for langko design and (2) to develop a new langko design incorporating these features while maintaining the original’s essence. Fieldwork was conducted on seven langko structures located in Pusa, Asajaya, and Kuching. Data was collected through observation and site analysis to assess the physical condition, spatial layout, materials, and sustainability elements of langko structures. Non-structured interviews with local producers were also conducted to obtain more information on the langko conditions. From the study on the condition of the existing langko, the areas needing improvement include three main elements, including space planning, construction methods, and sustainable features. The new Langko design is divided into a semi-private area and a public area. The semi-private area is an enclosed space for the production of gula apong, while the public space can be used as a product display area or café. The semi-private area is built with enclosed walls to prevent contamination and ensure hygiene during the production of the gula apong. Water harvesting system, solar panel for lighting, transparent roofing for natural lighting, and sustainable local materials are among the features incorporated into the new design